Global research trends and focus on the link between neutrophil extracellular traps and tumor: a bibliometric and visualization analysis from 2006 to 2024 - Xiao, Chaoyue; Feng, Xiang; Zhao, Zengyi; Ding, Gouping; Gao, Yawen (Frontiers in Immunology, 2024)
Background Neutrophil extracellular traps (NETs) have long been consistently considered an innate immune defense against foreign pathogens, but this oversimplified view has decelerated the progression of perceiving NET biology in chronic diseases. It is now increasingly accepted that NETs are not exclusive to anti-infection responses, but are also central players with a double-edged sword role in cancer progression. NETs have gradually emerged as tumor diagnostic, predictive, and prognostic biomarkers, and strenuous endeavors have been devoted to tapping their potential as new therapeutic targets. Correspondingly, the boom in studies on NETs and tumors in recent years has achieved a series of scientific outputs, which opens up a new perspective for perceiving the sophisticated landscapes of the tumor immune microenvironment. However, there is still much room to translate NET-targeted immunotherapies into clinical practice. Therefore, it is necessary to explore the knowledge structure and latent hotspots of the links between NETs and tumors using bibliometric analysis. Methods NETs and tumor publications from 2006 to 2024 were extracted from the Web of Science Core Collection. Bibliometric analysis and visualization were conducted using Microsoft Excel, VOSviewer, CiteSpace, and R-bibliometrix. Results The analysis included 1,339 publications authored by 7,747 scholars affiliated with 1,926 institutions across 70 countries/regions with relevant articles published in 538 journals. Despite China’s maximum number of publications, the United States has continued to dominate the field as a global cooperation center with overwhelming citation counts. Frontiers in Immunology published the most number of publications, whereas Blood was the most cited journal. Wagner, Denisa D. and Kaplan, Mariana J. are concurrently in both the top 10 most prolific authors and cited author lists. Tumor microenvironment and immunotherapy will likely be the focus of future research. Conclusions A comprehensive bibliometric analysis was first conducted to map the current landscape and knowledge structure of the link between NETs and tumors in the hope of providing guidance and fresh perspectives for further research in this field. NETs are promising antitumor targets, and perhaps the eventual destination in the realm is to translate NET-targeted immunotherapies into clinical practice.